Form Transformation of the Shield and the Application of the Throne Concept in the Design of the Shield of Throne Chair with a Bohemian Style - Bismialban, Allif Arwenda; Hapsari, Putri Sekar; Sumarno, Sumarno (Dinasti Publisher, 2025)
This study aims to design a lounge chair that blends local cultural values with a modern style by transforming the form of the Pancasila shield and the concept of Indonesian royal thrones into the design of a Bohemian-style Shield of Throne chair. The method used is Research-Based Design, consisting of four stages: contextual understanding, participatory design, product design, and prototype as a hypothesis. The design process is supported by the ATUMICS method, which emphasizes the integration of traditional and modern elements to create a contemporary product that still represents cultural values. The main materials used include teak wood, rattan, and polyester fabric, chosen for their strength, aesthetics, and practicality. The research results in a chair prototype showing that the integration of traditional forms with modern styles can produce furniture that is not only functional but also holds symbolic and aesthetic value, while remaining relevant to the needs of urban society. Thus, this design contributes to cultural preservation while also offering innovative and competitive furniture.